Firing costs in a business cycle model with endogenous separations - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2010)
This paper introduces productivity-dependent firing costs into an otherwise standard endogenous separations matching model. We suggest an alternative to the standard fix cost approach and account for empirical evidence emphasizing that firing costs vary across workers. We show that the model with firing costs outperformes the model without firing costs and replicates the empirical facts fairly well. Furthermore, we present cross-country evidence that countries with stricter employment protection have a weaker Beveridge curve relation and surprisingly more volatile job flow rates.
Older version: http://hdl.handle.net/10419/28377
Keywords: E24; E32; J64; 330; Beveridge Curve; Endogenous Separations; Firing Costs; Second Moments of Job Flows; Beveridge-Kurve; Kündigung; Kosten; Produktivität; Neoklassische Synthese; Theorie